Proteogenomic Analysis of Epibacterium Mobile BBCC367, a Relevant Marine Bacterium Isolated From the South Pacific Ocean - Matallana-Surget, Sabine; Werner, Johannes; Wattiez, Ruddy; Lebaron, Karine; Intertaglia, Laurent; Regan, Callum; Morris, James; Teeling, Hanno; Ferrer, Manuel; Golyshin, Peter N.; Gerogiorgis, Dimitrios; Reilly, Simon I.; et al. (Frontiers in Microbiology, 2018)
Epibacterium mobile BBCC367 is a marine bacterium that is common in coastal areas. It belongs to the Roseobacter clade, a widespread group in pelagic marine ecosystems. Species of the Roseobacter clade are regularly used as models to understand the evolution and physiological adaptability of generalist bacteria. We used gel-free shotgun proteomics to assess E. mobile BBCC367 protein expression under 16 different conditions, including stress factors such as elevated temperature, nutrient limitation, high metal concentration, and UVB exposure. Comparison of the different conditions allowed us not only to retrieve almost 70% of the predicted proteins, but also to define three main protein assemblages: 584 essential core proteins, 2,144 facultative accessory proteins and 355 specific unique proteins. Among these we studied a wide diversity of expressed protein functions, including transporters, DNA repair proteins, quorum sensing, transcriptional/translational regulators, and chemotaxis proteins that provided insights into how E. mobile BBCC367 adapts to environmental changes and copes with diverse forms of stress.